Preservation of Ancient Manuscripts “Sanghyang Siksa Kandang Karesian” at the National Library of Indonesia - Cristianingtyas, Yohana Grace (Indonesian Journal of Humanities and Social Sciences, 2024)
One legacy that still exists and is considered a tangible result of writing is manuscripts. Manuscripts are documents that contain thoughts, feelings and knowledge produced by a nation of manuscript writers themselves. Like the Sanghyang Siksa Kandang Karesian (SSKK) manuscript as a cultural product that can provide information on the perspective, attitudes and behaviour of the people at that time in seeking happiness in everyday life. This research aims to examine the preservation activities of the SSKK manuscript. The 1ocation of this research was at the National Library of Indonesia. The objects of this research are 3 SSKK manuscripts collected by the National Library of Indonesia. The method used in this research is a qualitative method with data collection techniques in the form of interviews, observation and through literature studies! The results of the research can be stated that the preservation activities of the SSKK manuscript collection of the National Library of RI are carried out preventively and curatively. Preventive preservation activities are carried out by surveying the condition of library materials, training professional conservators. conditioning the environment around the storage room, and planning disaster preparedness. Meanwhile. curative preservation is done by manual mending fumigation and transliteration. With this, the National Library of Indonesia has made various efforts to preserve the SSKK manuscript so that it is maintained and can-be accessed by the library users.